The strategy of Madrasa Ibtidaiya Principal in human resource development for increasing teachers’ professional and academic competency - Muyiman Muyiman (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2018)
The purposes of this research were to know the strategy of teachers’ professional development and to know teachers’ academic competence development conducted by the principal to the teachers of Madrasa Ibtidaiya (MI) in Wonosegoro Boyolali. The research type used in this thesis was qualitative research. The location of the research were some MI in Wonosegoro Boyolali, they were MI Muhammadiyah Ringinanom, MI Miftahul Ulum Bandung and MI Darul Ulum Karangasem. The data sources used were primary and secondary. The methods of the data collection were observation, interview, and documentation. The data analysis was done by using inductive method of thinking. The results of the research showed that the strategy of the principal of MI Muhammadiyah Ringinanom, MI Miftahul Ulum Bandung and MI Darul Ulum Karangasem in improving the teachers’ professional competence were by creating teacher training plan, arranging budget allocation, observing or assessing teachers’ performance, supervising or examining, giving exemplary, and socializing vision and mission of Madrasa. Human resource development efforts undertaken in developing the professionalism of teachers by conducting teachers’ performance management, Madrasa Working Group (KKM), education and training (diklat), seminar, and supervision to develop teachers' academic competence by conducting profession development and further studying.